Management of Floor Heave at Bulga Underground Operations—A Case Study - Sungsoon Mo; Serkan Saydam; Kudret Tutuk (International Conference on Ground Control in Mining, 2018)
"This paper presents an overview of the floor heave management at the Glencore Bulga Underground Operations and investigates the contributing factors to the behaviour of the floor. The mine experienced a number of major floor heave events in gateroads on development. As the longwall face approached the roadways, the magnitude of floor heave frequently increased, while new floor heave also developed. Furthermore, severe floor heave events took place along the longwall face. The most observed failure mode was buckling. While regular floor measurements were conducted to better understand the nature of the phenomenon, and various measures were considered to control the deformation of floor, the mining height was increased for the predicted floor heave domains, which facilitated effective management of the floor issues. The experience in the mine indicates that mainly high horizontal stresses with greater depths of cover and certain types of floor lithology configuration are likely to contribute to the failures of floor strata.INTRODUCTIONThe Glencore Bulga Underground is located in the Southwest of Singleton in the Hunter Valley of New South Wales, Australia. Blakefield South, part of Bulga Underground, commenced longwall mining in 2010, extracting coal from the Blakefield seam, while the overlying longwall panels were previously mined from the Whybrow seam. The coal seam ranges from 4.5 m to 8.0 m thick with the mining heights varying from 2.9 m to 3.5 m. The longwall panels are 320 m and 400 m wide and up to 3.5 km long.The mine experienced a wide range of floor issues around longwall panels LW7 and LW8, both 400 m wide. For instance, the concrete floor in the travel road failed and lifted as the longwall retreated in close proximity as can be seen in Figure 1. Figure 2 shows the beam stage loader (BSL) buried into the lifted floor, and Figure 3 shows a timber prop distorted due to the movement of the floor. In addition, severe deformation of the floor along the longwall face impeded the longwall operation, as shown in Figure 4."